2012
DOI: 10.3329/bjp.v7i3.11499
|View full text |Cite
|
Sign up to set email alerts
|

Alpha glucosidase inhibitory effect and enzyme kinetics of coastal medicinal plants

Abstract: Research ArticleAlpha Alpha Alpha---glucosidase inhibitory effect glucosidase inhibitory effect glucosidase inhibitory effect and enzyme kinetics of coastal meand enzyme kinetics of coastal meand enzyme kinetics of coastal medicinal plants dicinal plants dicinal plants BJP IntroductionAbout 2.5-7% of the world's populations diagnosed with leading endocrine disease diabetes mellitus which causes morbidity and mortality (Seghrouchni et al., 2002). By the act of pancreatic -amylase, starch has hydrolyzed and abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…The α-glucosidase inhibition by 80% of an ethanol extract of Garcinia sp., Citrullus colocynthis was reported to be 80-85%, which might be through a mixture of phenolic compounds in leaves (Elya et al, 2012;Gurudeeban et al, 2012). This study also observed most of the α-glucosidase inhibition by ethanolic extract.…”
Section: Discussionsupporting
confidence: 60%
“…The α-glucosidase inhibition by 80% of an ethanol extract of Garcinia sp., Citrullus colocynthis was reported to be 80-85%, which might be through a mixture of phenolic compounds in leaves (Elya et al, 2012;Gurudeeban et al, 2012). This study also observed most of the α-glucosidase inhibition by ethanolic extract.…”
Section: Discussionsupporting
confidence: 60%
“…Non-polar extracts (n-hexane extracts) from Citrullus colocynthis, Aegle marmelos and Ipomoea pes-caprae showed similar inhibitory activity than those of the essential oil of C. macrostemum var. laevigatum (Gurudeeban et al, 2012). The effect of essential oils from different seasonal periods on enzyme activity revealed differences in the IC 50 values being those of winter and fall less effective than the others (Table 3).…”
Section: Tablementioning
confidence: 93%
“…The production of ROS increases under diabetic conditions (Noh and Ha 2011;Ha et al 2008). Meanwhile, alphaglucosidase inhibitors helped control postprandial blood glucose levels in diabetic patients (Sancheti et al 2011;Gurudeeban et al 2012). It reduce the digestion and delay the absorption of carbohydrates, which relieved the postprandial increase in blood glucose levels (Cheng and Josse 2004).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Some reports suggested that decreasing the level of postprandial hyperglycemia is one of most effective therapeutic approaches in the early period of diabetes mellitus (Lee et al 2009;Ghadyale et al 2011;Van de Laar et al 2012). Other studies demonstrated that alpha-glucosidase inhibitors helped to control postprandial blood glucose levels in diabetic patients (Sancheti et al 2011;Gurudeeban et al 2012).…”
Section: Introductionmentioning
confidence: 99%